PENGGUNAAN STRATEGI PEMBELAJARAN MURDER PADA MATERI PAI DI SMK ROUDLOTUN NASYI’IN - Lilawati, Emi; Rohman, M. Nur (Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to find out the steps for using the MURDER learning strategy and to find out the advantages and disadvantages of the MURDER learning strategy in PAI subjects at Roudlotun Nasyi'in Vocational School in Mojokerto. The background of the problem in this research is that the teacher in carrying out learning has not fully implemented the appropriate learning model and is in accordance with the student's way of learning. This raises problems when the teacher applies a monotonous learning model and does not match the student's learning style, so the learning process does not attract students' interest in learning so that students find it difficult to understand the material being taught. The problems in this research are: 1. what are the steps in using the MURDER learning strategy. 2. the advantages and disadvantages of the MURDER learning strategy. How is the level of students' ability to express ideas, thoughts and experiences through this learning model. The method used during the research was: an approach to the pie teacher at Roudlotun Nasyi'in Vocational High School in Mojokerto. Data analysis techniques are describing phenomena, classifying them, seeing concepts. This type of research is qualitative research. The research subjects were PAI teachers at Roudlotun Nasyi'in SMK Mojokerto. Data collection techniques in this study used interviews and documentation to complete the revealed data. Based on the results of the study, it can be seen that the application of the MURDER learning strategy can improve students' thinking skills so that students are able to understand the MURDER learning strategy very well.